2015
DOI: 10.1088/0964-1726/24/2/025032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the sensitivity and fatigue performance of embedded piezopolymer sensor systems in sandwich composite laminates

Abstract: Evaluation of the sensitivity and fatigue performance of embedded piezopolymer sensor systems in sandwich composite laminates AbstractIt has been claimed that embedding piezoceramic devices as structural diagnostic systems in advanced composite structures may introduce mechanical impedance mismatches that favor the formation of intralaminar defects. This and other factors, such as cost and their high strain sensitivity, have motivated the use of thin-film piezopolymer sensors. In this paper, we examine the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…PVDFs and piezo films, in general, can be used for this purpose. PVDF films were embedded inside and on the surface of the lower skin of sandwich composite panels to perform strain measurement during static and dynamic three-point bending tests (Chrysochoidis and Gutie´rrez, 2015). In situ PVDFs were shown not to be intrusive (no marked reduction in tensile specimens' strength) and were able to give information during the cyclic tests as their sensitivity (mstrain/Volt) was increasing until final failure of the specimens.…”
Section: Reminder About Piezoelectric Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…PVDFs and piezo films, in general, can be used for this purpose. PVDF films were embedded inside and on the surface of the lower skin of sandwich composite panels to perform strain measurement during static and dynamic three-point bending tests (Chrysochoidis and Gutie´rrez, 2015). In situ PVDFs were shown not to be intrusive (no marked reduction in tensile specimens' strength) and were able to give information during the cyclic tests as their sensitivity (mstrain/Volt) was increasing until final failure of the specimens.…”
Section: Reminder About Piezoelectric Effectmentioning
confidence: 99%
“…All the studies used commercially available PVDF (films or powders) as raw material for the sensors. Films can be industrially poled (Caneva et al, 2008;Chrysochoidis and Gutie´rrez, 2015;De Rosa and Sarasini, 2010;Guzman et al, 2013;Mills, 2013;Park et al, 2005), wired (riveted lead wires; Guzman et al, 2013;Mills, 2013) or metallized (Bellan et al, 2005) beforehand.…”
Section: Pvdfmentioning
confidence: 99%
See 1 more Smart Citation
“…As in concrete, capacitative imaging with coplanar non-contact electrodes can also be used for moisture or damage detection and localisation in different FRP composites as CFRP, honeycomb structures and GFRP [25,26]. Recently, piezoelectric sensors embedded in FRP have also been used as capacitance sensors [27,28] instead of just as acoustic emission [29,30] or voltage sensors [31][32][33][34] as established by many research groups (review in [35]). It was shown that capacitance measurements on embedded piezoelectric transducers are in good agreement with loading and unloading trends in different tensile tests on GFRP [28].…”
Section: Introductionmentioning
confidence: 99%
“…Research have already been conducted in this area [16][17][18][19][20][21]23,34,35,39,[41][42][43][44][45][46][47][48], but this article stands out of them for several reasons. First, the authors used the embedded piezoelectric transducer as a capacitance sensor and not otherwise, such as an AE sensor [16,17,[19][20][21]23,34,39,43] or an electric charge sensor [41,42,44,45] to perform in-situ and real-time SHM. Finally, the use of a multi-instrumentation comprising various NDT techniques, and the combination of their signals with the transducer capacitance signature to perform SHM have never been realized until now according to the authors.…”
Section: Introductionmentioning
confidence: 99%